2022
DOI: 10.1158/1538-7445.am2022-100
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 100: IL-1β pathway promotes cell proliferation and 5-FU resistance in African American colon cancer cell lines

Abstract: Introduction: Colorectal Cancer (CRC) is the third most common cancer and third cause of cancer-related death in the US. When taking race and ethnicity into consideration, African Americans (AA) present with the highest incidence and mortality rates for CRC. Studies have found that AA patients, when compared to Caucasian American (CA) patients, have a lower response to the standard of care chemotherapeutic agent 5-Fluorouracil (5-FU) as well as lower frequency of MSI tumors, making them also less likely to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Even though the IL-8 cytokine gene is upregulated, it is not signi cantly different from the untreated group. Previous research on another in ammatory cytokine, IL-1, demonstrated that 5-FU sensitivity is signi cantly decreased in the presence of IL-1 for several colon cancer cell lines, indicating that IL-1 may be involved in the development of drug resistance (Spagnardi et al 2022). However, our investigation does not examine IL-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the IL-8 cytokine gene is upregulated, it is not signi cantly different from the untreated group. Previous research on another in ammatory cytokine, IL-1, demonstrated that 5-FU sensitivity is signi cantly decreased in the presence of IL-1 for several colon cancer cell lines, indicating that IL-1 may be involved in the development of drug resistance (Spagnardi et al 2022). However, our investigation does not examine IL-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%